Synthesis of zinc oxide nanotwins using electrochemical deposition technique at different current densities. (16th July 2022) - Kabaa, E.A.; Hassan, Z.; Ahmed, N.M.
The electrochemical deposition (ECD) of metal oxides has revealed distinct structural features in semiconductors. Zinc oxide (ZnO) nanotwins were directly deposited on commercial conductive indium tin oxide (ITO) glass via ECD using two-electrode configurations. The ZnO nanotwins were synthesised under different current densities (5, 10, 15 and 20 mA/cm 2 ) at 70°C for 15 min. The ZnO nanotwins were characterised using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) with energy-dispersive X-ray spectroscopy (EDX), ultraviolet-visible (UV-vis) spectroscopy, and photoluminescence (PL) spectroscopy. The lengths of as-prepared ZnO nanotwins range from 100 to 700 nm. The hexagonal structure of ZnO was confirmed using XRD. EDX showed the ratio of carbon dots migration from graphite electrode (anode) to ZnO structure increased with current density. The FESEM micrographs reveal that the morphology of the ZnO nanotwins varied with current density. The nanotwin-cones shape is formed as the current density is increased from 5 mA/cm 2 to 20 mA/cm 2 . The optical spectra showed direct band gap of 3.34, 3.31, 3.20, 3.11 eV at current density values of 5, 10, 15, and 20 mA/cm 2, respectively. The decrease in energy band gap of ZnO ratio results from increase in carbon dots. The defect inherent in the carbon dots within ZnO structures led to the appearance of a broad peak in wavelength range of 480-650 nm with a weak peak emerging at 370 nm in the PL spectra.